The role of adiponectin in the association between abdominal obesity and type 2 diabetes: a mediation analysis among 232,438 Chinese participants - He, Lingjie; Xuan, Wenting; Liu, Dixing; Zhong, Jiana; Luo, Huijin; Cui, Han; Zhang, Xiuwei; Chen, Weikun (Frontiers in Endocrinology, 2024)
Background: Adiposity and adipokines are closely associated with obesity-related metabolic abnormalities, but little is known regarding that whether abdominal obesity link type 2 diabetes mellitus (T2DM) through circulating adiponectin levels. Thus, this large population-based study was designed to investigate the mediating effect of adiponectin in the relationship between abdominal obesity and T2DM. Methods: A total of 232,438 adults who lived in Dongguan, Guangdong Province, China, were enrolled in the present study. The circulating adiponectin concentrations were measured using latex-enhanced immunoturbidimetric assay. The association between circulating adiponectin and other clinical parameters was detected by spearman correlation analysis. Restricted cubic spline (RCS) regression was also used to address the nonlinearity of the relationship between waist circumference and diabetes. Mediation analyses of circulating adiponectin were conducted using linear and logistic regression. Results: Subjects with abdominal obesity had lower levels of circulating adiponectin (P<0.001). The circulating adiponectin value was inversely related to BMI (r= -0.370, P<0.001), waist circumference (r= -0.361, P<0.001) and fasting plasma glucose (r= -0.221, P<0.001). The RCS plot showed a nonlinear relation linking waist circumference with T2DM (P for non−linearity<0.001). Abdominal obesity patients presented 2.062 times higher odds of T2DM in comparison to non-abdominal obesity ones [odds ratio (OR): 2.062, 95% CI: 1.969-2.161] after adjusting for confounders. In the mediation analyses, the circulating adiponectin mediated the association between abdominal obesity and T2DM, with a mediation effect of 41.02% after adjustments. The above results were consistent in both males and females. Conclusions: The relationship between abdominal obesity and T2DM is mediated through circulating adiponectin level in adults, suggesting that circulating adiponectin might be a potential predictor for controlling the adverse progression from adiposity to T2DM.